Recent Advances in the 3D Physiological Human - Magnenat-Thalmann, Nadia; Zhang, Jian J.; Feng, David D.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2009)
Research into the 3D Physiological Human is a very active field focusing on the creation of patient-specific computer models for personalised healthcare. Reporting on how these models can simulate and provide a better understanding of human physiology and pathology, this book also looks at how the evolution and the improvement of technological devices such as scanners, medical instruments, and computer power have helped in our understanding of the human body and its functionalities. The book contains contributions from leading researchers from a variety of disciplines (including computer graphics, biomechanics, knowledge representation, human-machine interfaces etc) associated with medical imaging, simulation, computer-assisted surgery and 3D semantics. Divided into three parts: anatomical and physiological modelling, physically-based simulation, and medical analysis and knowledge management, this book provides a clear picture of the most recent advances in this increasingly important area.
Anatomical and Physiological Modelling -- Musculoskeletal Simulation Model Generation from MRI Data Sets and Motion Capture Data -- GeomCell -- Tracking Organs Composed of One or Multiple Regions Using Geodesic Active Region Models -- Human Hand Kinematic Modeling Based on Robotic Concepts for Digit Animation with Dynamic Constraints -- Physically Based Simulation -- Virtual Pulmonary Valve Replacement Interventions with a Personalised Cardiac Electromechanical Model -- Interactive Simulation of Diaphragm Motion Through Muscle and Rib Kinematics -- Toward Anatomical Simulation for Breath Training in Mind/Body Medicine -- Simulating the Human Motion Under Functional Electrical Stimulation Using the HuMAnS Toolbox -- Hierarchical Markov Random Fields Applied to Model Soft Tissue Deformations on Graphics Hardware -- A Physics-Based Modeling and Real-Time Simulation of Biomechanical Diffusion Process Through Optical Imaged Alveolar Tissues on Graphical Processing Units -- Medical Analysis and Knowledge Management -- Estimating Hip Joint Contact Pressure from Geometric Features -- Rapid Impingement Detection System with Uniform Sampling for Ball-and-Socket Joint -- X-ray-Based Craniofacial Visualization and Surgery Simulation -- OMOGENIA: A Semantically Driven Collaborative Environment.
Keywords: Computer science; Human anatomy; Computer simulation; Computer graphics; Image processing; Computer Science; Computer Graphics; Image Processing and Computer Vision; Anatomy; Simulation and Modeling; Electronic books